2020
DOI: 10.1007/s00262-020-02585-w
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood markers predictive of outcome and immune-related adverse events in advanced non-small cell lung cancer treated with PD-1 inhibitors

Abstract: Background Selected patients with advanced non-small cell lung cancer (NSCLC) benefit from immunotherapy, especially immune checkpoint inhibitors such as PD-1 (programmed cell death protein 1) inhibitor. Peripheral blood biomarkers would be most convenient to predict treatment outcome and immune-related adverse events (irAEs) in candidate patients. This study explored associations between inflammation-related peripheral blood markers and onset of irAEs and outcome in patients with advanced NSCLC receiving PD-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
160
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(169 citation statements)
references
References 37 publications
(48 reference statements)
8
160
1
Order By: Relevance
“…The development of irAEs has been associated with improved response to ICI treatment, as reviewed by Das & Johnson ( 80 ). In line with this, some of the irAE biomarkers in this review have also shown associations with ICI responses ( 18 22 , 31 , 37 , 44 ). This is not surprising, in view of the common underlying mechanism of irAEs and anti-tumor responses ( 48 ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The development of irAEs has been associated with improved response to ICI treatment, as reviewed by Das & Johnson ( 80 ). In line with this, some of the irAE biomarkers in this review have also shown associations with ICI responses ( 18 22 , 31 , 37 , 44 ). This is not surprising, in view of the common underlying mechanism of irAEs and anti-tumor responses ( 48 ).…”
Section: Discussionsupporting
confidence: 81%
“…In their study amongst 102 anti-PD-1 treated melanoma patients, Peng et al. reported that patients with NLR>5 experienced less irAEs ( 18 ). Additionally, they observed that a prognostic nutrition index (PNI), which is calculated from the serum albumin level and total lymphocyte count, of 45 or higher was correlated with increased risk of irAEs.…”
Section: Biomarkersmentioning
confidence: 99%
“…Multiple prior studies have also shown the association between NLR, irAE development and OS (12)(13)(14). In a study of patients with advanced non-small cell lung cancer (NSCLC) treated with anti-PD-(L)1 agents, baseline NLR<3 was signi cantly associated with development of irAEs.…”
Section: Discussionmentioning
confidence: 99%
“…This finding agrees with previous studies, which associated lower inflammation-related blood markers with a higher risk of irAEs in NSCLC patients. 24 , 25 While patients who had irAEs were more likely to have good treatment outcomes with anti-PD-1, they were also more likely to have lower baseline NLR and PLR levels. This result was consistent with the previous observation, that lower NLR and PLR were associated with good clinical outcomes in NSCLC patients treated with immune checkpoint inhibitors or platinum-based first-line chemotherapy.…”
Section: Discussionmentioning
confidence: 99%